Laparoscopic versus Open Reduction of Intussusception in Infants and Children: A Systematic Review and Meta-analysis - Wu, Peng; Huang, Ping; Fu, Yijia; Lv, Yaxin; Feng, Shaoguang; Lou, Yi (European Journal of Pediatric Surgery, 2022)
We conducted a systematic review and meta-analysis to compare the efficacy and safety between laparoscopic reduction (LR) and open reduction (OR) of intussusception in infants and children. Literature searches were conducted to identify studies having compared LR and OR for children with intussusception failed to enema reduction. Parameters such as operative time, time to oral intake, length of hospital stay, overall postoperative complications, and recurrence were pooled and compared by meta-analysis. Among the 502 pediatric participants included in the 11 studies, 275 had received LR and 227 received OR. There were shorter length of hospital stays and time to oral intake with the LR approach compared with OR. However, no significant difference was found between LR and OR in the secondary outcome, such as the overall postoperative complications and recurrence. LR is a feasible, safe, and effective surgical procedure alternative to OR for pediatric intussusception. Compared with OR, LR has the advantage of shorter hospital stay and faster time to oral intake. Besides, the overall postoperative complications may be slightly lower in LR. We conclude that LR should be considered an acceptable option for children.
Keywords: intussusception; laparoscopy; recurrence; meta-analysis